Complementary and alternative medicine use and pain characteristics in older Vietnamese adults with chronic pain: A cross-sectional study - Nguyen Thi Thu Trieu; Nguyen Thi Yen Hoai; Pham Thi Thuy; Phan Thi An Dung; Do Thi Ninh (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Chronic pain is a common and burdensome condition among older adults, significantly impacting their quality of life and increasing interest in complementary and alternative medicine (CAM) approaches to pain management. Objectives: This study aimed to describe the prevalence of CAM use and attitudes toward CAM for self-managing chronic pain among older adults, and to examine the associations between chronic pain characteristics, CAM use, and attitudes toward CAM. Methods: A cross-sectional study was conducted among 289 hospitalized patients aged ≥60 years with chronic pain at a general hospital in Da Nang, Vietnam, in 2025. Data were collected using a structured questionnaire that included the Pain Disability Index (PDI) and the Attitudes towards CAM scale. Statistical analyses included t-tests, ANOVA, chi-square tests, and Pearson’s correlation. Results: CAM use was reported by 92.7% of participants, with biologically based therapies (e.g., herbal remedies) being the most common (81.3%). The average attitude score toward CAM was 28.7 (SD = 3.2), indicating generally favorable views. CAM use was more frequently reported among participants experiencing pain in specific anatomical locations, including the arm/hand, neck, upper back, and lower back (all p <0.008 after Bonferroni correction). Attitudes toward CAM were modestly associated with perceived pain control ability (p = 0.031) and with the impact of chronic pain on daily life (r = 0.206; p <0.001), while other pain characteristics showed no significant associations. Conclusion: CAM is widely used and positively perceived among older Vietnamese adults with chronic pain. Associations were observed between certain pain characteristics and CAM use, as well as between pain-related interference and attitudes toward CAM. These findings highlight the importance of routinely assessing CAM use in older adults and providing guidance on safe, evidence-based options within comprehensive pain management, while recognizing the observational nature of the data.